INOVASI LEMBAGA PENDIDIKAN ISLAM ACEH DALAM MEMPERSIAPKAN GENERASI QUR’ANI DI ERA DIGITAL - Basri, Basri; Wahidah, Wahidah; Mahyiddin, Mahyiddin (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
Aceh after the conflict, precisely after the peace agreement between the Free Aceh Movement and the Government of the Republic of Indonesia on August 15, 2005, has provided space for the revival of Islamic education in Aceh. This article discusses the innovation of Islamic education in Aceh using qualitative methods. The main data of this study are articles that have been published in national and international reputable scientific journals and books in libraries related to Islamic Education Institutions. Data collection uses https://scholar.google.com/ links, https://garuda.kemdikbud.go.id/, and https://www.sciencedirect.com/ which are then analyzed with content analysis techniques. The results of the study show that the revival of Islamic education in Aceh occurs in three innovations. First, institutional innovation with various policies and regulations from the government that is getting stronger. Second, curriculum innovation that combines religious education materials with general science materials with learning methods and media that utilize information technology. Third, innovation in the integration model of dayah/pesantren education with public schools, and integrated public school models such as SD IT, SMP IT and SMU Plus.